2000
DOI: 10.1097/00007890-200012150-00011
|View full text |Cite
|
Sign up to set email alerts
|

Outflow Tract Reconstruction in Living Donor Liver Transplantation1

Abstract: A triple recipient venoplasty with a matching venoplasty of multiple graft hepatic veins to create a single wide outflow orifice is recommended in living donor liver transplantation using left side grafts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 7 publications
3
58
0
Order By: Relevance
“…The disease indications for transplantation included hepatitis B virus with or without hepatocellular carcinoma (HCC; 92), hepatitis C virus infection with or without HCC (25), primary biliary cirrhosis (12), alcoholic cirrhosis (8), hepatitis B virus and hepatitis C virus with or without HCC (6), Wilson's disease (4), and other (5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease indications for transplantation included hepatitis B virus with or without hepatocellular carcinoma (HCC; 92), hepatitis C virus infection with or without HCC (25), primary biliary cirrhosis (12), alcoholic cirrhosis (8), hepatitis B virus and hepatitis C virus with or without HCC (6), Wilson's disease (4), and other (5).…”
Section: Resultsmentioning
confidence: 99%
“…4 Our techniques for donor graft hepatectomy and recipient total hepatectomy in LDLT have been described in detail previously. 3,5,6 The anesthesia management followed the protocol of the Department of Anesthesiology. 7,8 Red blood cell transfusions were not given to patients with hemoglobin levels > 8.0 g/ dL and as long as the intravascular volume was sufficient to maintain normal hemodynamics.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously demonstrated that the placement of a wide common channel portion is beneficial for accommodating potential graft remodeling-associated distortion of the hepatic vein anastomosis. [5][6][7] Therefore, when wedged unification is being performed, the depth of the wedging should be adjusted and optimized after the consideration of the relative sizes of the graft and the recipient's hepatic veins. At this point, we emphasize the importance of size matching between the graft hepatic vein orifice and the diameter of the recipient's IVC.…”
Section: Discussionmentioning
confidence: 99%
“…17 To date, we have 3 technical approaches to bench work for hepatic vein orifices of left liver grafts for both adult and pediatric patients, including extended left livers, left livers without the MHV trunk, extended LLSs, LLSs, reduced LLSs, and monosegments. The first approach is unification venoplasty with central wedging/septoplasty to make a wide common channel [5][6][7] ; the second, the placement of a side patch to widen the hepatic vein orifice, 9,18 is a procedure that can be combined with the first approach; and the third is a very unusual combination of the first approach and vein graft interposition. According to our experience, these techniques cover nearly all hepatic vein variations in various types of left liver grafts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation